On the Molecular Selection of Exopolysaccharide-Producing Lactic Acid Bacteria from Indigenous Fermented Plant-Based Foods and Further Fine Chemical Characterization - Angel Angelov; Aneliya Georgieva; Mariana Petkova; Elena Bartkiene; João Miguel Rocha; Manol Ognyanov; Velitchka Gotcheva (Foods, 2023)
Exopolysaccharides (EPSs) produced by lactic acid bacteria present a particular interest for the food industry since they can be incorporated in foods via in situ production by selected starter cultures or applied as natural additives to improve the quality of various food products. In the present study, 43 strains were isolated from different plant-based fermented foods and identified by molecular methods. The species found were distinctively specific according to the food source. Only six Lactiplantibacillus plantarum strains, all isolated from sauerkraut, showed the ability to produce exopolysaccharide (EPS). The utilization of glucose, fructose and sucrose was explored with regard to EPS and biomass accumulation by the tested strains. Sucrose was clearly the best carbon source for EPS production by most of the strains, yielding up to 211.53 mg/L by strain Lactiplantibacillus plantarum ZE2, while biomass accumulation reached the highest levels in the glucose-based culture medium. Most strains produced similar levels of EPS with glucose and fructose, while fructose was utilized more poorly for biomass production, yielding about 50% of biomass compared to glucose for most strains. Composition analysis of the EPSs produced by strain Lactiplantibacillus plantarum ZE2 from glucose (EPS-1) and fructose (EPS-2) revealed that glucose (80–83 mol%) and protein (41% w/w) predominated in both analyzed EPSs. However, the yield of EPS-1 was twice higher than that of EPS-2, and differences in the levels of all detected sugars were found, which shows that even for the same strain, EPS yield and composition vary depending on the carbon source. These results may be the basis for the development of tailored EPS-producing starter cultures for food fermentations, as well as technologies for the production of EPS for various applications.